An Exploratory Study of Successful Paperwork Management Techniques for Novice Special Education Teachers - Mehrenberg, Richard L. (Journal of the American Academy of Special Education Professionals, 2013)
Eighteen novice special education teachers were interviewed to determine successful strategies regarding paperwork completion and paperwork advice for those new to the field. Interview transcripts revealed five specific paperwork completion strategies: (a) get organized; (b) understand your job description; (c) ask for help; (d) appreciate the value of special education paperwork; and (e) know when to take a break. Each technique is described, enhanced with interview excerpts, and composite examples as appropriate.